Analysis of hotels' environmentally sustainable policies and practices: Sustainability and corporate social responsibility in hospitality and tourism. Issue 6 (7th June 2019) - Khatter, Ajay; McGrath, Michael; Pyke, Joanne; White, Leanne; Lockstone-Binney, Leonie
Abstract : Purpose: This paper aims to present the findings of an analysis of the environmentally sustainable policies and practices (ESPPs) used by independent and chain-affiliated hotels. The study aimed to ascertain the engagement of hotels with ESPPs and provide tentative evidence of their commitment towards meeting the expectations of environmentally conscious stakeholders. Design/methodology/approach: This study used secondary data and content analysis to examine the ESPPs of a sample of 220 hotels in Melbourne, Australia. A systematic review was conducted of hotel websites to reveal, in a tabulated way, the range of reporting of environmental material provided by various rated hotels. Findings: This analysis suggests that environmentally friendly business practices are prominently displayed by the hotels sampled; however, independent non-chain affiliated hotels are yet to adopt ESPPs in any visible way. Originality/value: This study was broadly informed by stakeholder theory (Freeman, 1984) and aimed to ascertain the engagement of hotels with ESPPs. While previous studies have focussed on chain hotels, this research involved a greater range of hotels of different profiles to highlight the mix of ESPPs across the hotel sector. Rather than merely examining the corporate websites of hotel companies, the research additionally examined ESPPs at the individual hotel property level, as this is where policies are implemented into practice. The extant literature to date has not studied the extent to which ESPPs are adopted by independent and chain-affiliated hotels at this level, and it is this research gap that the study addresses.